Radium-223 Plus Enzalutamide Versus Enzalutamide in Metastatic Castration-Refractory Prostate Cancer: Final Safety and Efficacy Results. (23rd September 2021) - Maughan, Benjamin L.; Kessel, Adam; McFarland, Taylor Ryan; Sayegh, Nicolas; Nussenzveig, Roberto; Hahn, Andrew W.; Hoffman, John M.; Morton, Kathyrn; Sirohi, Deepika; Kohli, Manish; Swami, Umang; Boucher, Kenneth; et al.
Abstract : Lessons Learned : Long-term safety of radium-223 with enzalutamide was confirmed in this clinical trial. PSA-PFS2 was prolonged with the combination compared with enzalutamide alone. Background: Previously, we showed the combination of radium-223 and enzalutamide to be safe and associated with improved efficacy based on a concomitant decline in serum bone metabolism markers compared with enzalutamide alone in a phase II trial of men with metastatic castration-resistant prostate cancer (mCRPC) [1]. Methods: Secondary endpoints were not included in our initial report, and we include them herein, after a median follow-up of 22 months. These objectives included long-term safety, prostate-specific antigen (PSA)–progression-free survival (PFS), and radiographic progression-free survival; PSA-PFS2 (time from start of protocol therapy to PSA progression on subsequent therapy); time to next therapy (TTNT); and overall survival (OS). Survival analysis and log-rank tests were performed using the R statistical package v.4.0.2 (https://www.r-project.org ). Statistical significance was defined as p < .05. Results: Of 47 patients (median age, 68 years), 35 received the combination and 12 enzalutamide alone. After a median follow-up of 22 months, final safety results did not show any increase in fractures or other adverse events in the combination arm. PSA-PFS2 was significantly improved, and other efficacy parameters were numerically improved in the combination over the enzalutamide arm. Conclusion: The combination of enzalutamide and radium-223 was found to be safe and associated with promising efficacy in men with mCRPC. These hypothesis-generating results portend well for the ongoing phase III PEACE III trial in this setting.